Intellectual Property Tourism in Indonesia: Environmental Conservation and Regional Economic Strengthening - Saputro, Triyono Adi; Firdaus, Wahyu Tri Mohamad; Rahmawati, Awalia Rina; Safly, Afiq (Journal of Law, Environmental and Justice, 2025)
The existence of intellectual property and tourism has a vital role in claiming business competition at the national and international levels. The urgency of this research is to analyze and examine the role of tourism intellectual property on environmental conservation and regional economy.  The purpose of this research is to analyze the concept of tourism intellectual property from the economic and environmental perspectives, examining its impact and benefits for strengthening the regional economy and preserving natural sustainability. This research is normative law with a conceptual and statutory approach supported by primary and secondary legal data. The results of this study indicate that the existence of tourism intellectual property has a multiplier effect which has a correlation in preserving the environment because it participates in maintaining and protecting natural resource products through the legality of intellectual property. In addition, the existence of tourism intellectual property not only helps preserve the environment on the other hand can be a form of strengthening the regional economy because the existence of products protected with intellectual property can increase selling value and be able to absorb labor and unemployment in the region can be reduced. The presence of the concept of intellectual property tourism can become an attraction for the region and elevate the region's image to external markets, thereby increasing the number of visiting tourists and making the area more famous.